SOME PHENOMENOLOGICAL CHARACTERISTICS OF THE HUMAN TRAFFICKING IN ALBANIA DURING THE PERIOD FROM 2003 TO 2014 - Naim Tota; Gledina Mecka (European Scientific Journal, ESJ, 2015)
The criminal phenomenology is part of a particular branch of Criminology, which studies the forms of criminality, its structure, the criminality’s change structure, and criminality’s dynamics. It studies the way the criminal acts are presented and also the social and individual characteristics of their authors. Along with this definition, this branch of criminology consists in studying the form of criminal acts presentation; it describes the outward forms of certain criminal acts and their extent, their time distribution as well as their tendencies, size and volume. Some juridical and criminological systems separate the authors according to this criterion in even more categories, as for example: minors, major minors, young adults and mature adults. However, several criminological researches complete the criminology classification according to age groups. Thus, there can be often found some classifications, according to which the 20-25 years of age category is the most represented, then there come the 25-30 and 30-35 years of age groups, where a gradual decrease in criminality can be detected. By the end of this classification there is the over-35-years-of-age group, whose characteristic is a progressive decrease in criminality, there are also the over 50 and over 60 groups of age, which are characterized by a significant decrease in criminality. Related to criminality’s division according to the author’s gender, criminality is a typical masculine reaction. In this paper, considering the human being trafficking phenomenology dimension, the contents from the area of criminal phenomenology, of the volume, dynamics and statistics of criminality and the most important data related to criminality will be included with the proper elaboration.